Properties of Zn-Bi composite coatings prepared by ionic co-discharge deposition - Tay, S.L.; Chen, Wei-wei; Wei, Xiao-jin; Yao, Cai-zhen; Gao, W. (2015)
Zn-Bi composite was synthesized by ionic co-discharge deposition and its properties were investigated. The results show that the Zn-Bi composite with the incorporation of Bi has a finer grain size than the pure Zn coating and improves the mechanical properties. The microhardness is increased by approximately two times simply by adding a small amount of Bi electrolyte into a Zn bath solution. A lower volume loss of the Zn-Bi composite coating compared with the pure Zn coating also indicates that the Zn-Bi coating has a better wear resistance.